Does fertiliser use improve household welfare? Evidence from Ghana's cocoa industry. Issue 2 (17th February 2019) - Danso-Abbeam, Gideon; Baiyegunhi, Lloyd J. S.
ABSTRACT: This article analyses welfare impacts of fertiliser adoption using data collected from 838 cocoa farm households in the four key cocoa-producing regions in Ghana. Using propensity score matching (PSM), the study indicates that application of fertiliser leads to significant gains in farm yields, farm income, consumption expenditure, consumption expenditure per capita, and value of productive farm assets. The article concludes that cocoa-specific programmes such as Cocoa High Technology (Cocoa Hi-tech), initiated to intensify the application of improved farm technologies such as fertiliser, should be strengthened through effective and efficient management systems.